Paleoenvironmental and diagenetic evolution of the Aptian Pre-Salt succession in Namibe Basin (Onshore Angola) - Mar Moragas; Vinyet Baqués; Juan Diego Martín-Martín; Ian Sharp; Fabio Lapponi; David Hunt; Michael Zeller; Jaume Vergés; Grégoire Messager; Laurent Gindre-Chanu; Roger Swart; Vladimir Machado (Marine and Petroleum Geology, 2023)

Structural characterization and biological activity of an α-glucan from the mollusk Marcia hiantina (Lamarck, 1818) - Hoda Al. Ahmed; Bernadeth F. Ticar; Ian Black; Fakhri Mahdi; Anter A. Shami; Sandeep K. Misra; Christian Heiss; Jason J. Paris; Joshua S. Sharp; Parastoo Azadi; Vitor H. Pomin (Glycoconjugate Journal, 2023)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

A comparison of postrelease survival parameters between single and mass stranded delphinids from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Charles T. Harry; Jane M. Hoppe; Kathleen M. Moore; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; Scott Landry; Jessica Richardson; Michael J. Moore (Marine Mammal Science, 2016)
The viability of healthy single stranded dolphins as immediate release candidates has received little attention. Responders have been reluctant to release lone delphinids due to their social needs, even when they pass the same health evaluations as mass stranded animals. This study tracked postrelease success of 34 relocated and released satellite tagged delphinids from single and mass strandings. Three postrelease survival parameters (transmission duration, swim speed, and daily distance) were examined to evaluate whether they differed among single stranded/single released ( SS / SR ), mass stranded/single released ( MS / SR ), or mass stranded/mass released ( MS / MR ) dolphin groups. Comparisons were also made between healthy and borderline release candidates. Satellite tags transmitted for a mean of 21.2 d ( SD = 19.2, range = 1–79), daily distance traveled was 42.0 km/d (11.25, 20.96–70.72), and swim speed was 4.3 km/h (1.1, 2.15–8.54). Postrelease parameters did not differ between health status groups, however, SS / SR dolphins transmitted for a shorter mean duration than MS / MR and MS / SR groups. Postrelease vessel‐based surveys confirmed conspecific group location for two healthy, MS / SR dolphins. Overall, these results support the potential to release healthy stranded single delphinids; however, further refinement of health assessment protocols for these challenging cases is needed.

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

Intra-uterine growth restriction is associated with increased apoptosis and altered expression of proteins in the p53 pathway in villous trophoblast - Alexander E. P. Heazell; Andrew N. Sharp; Philip N. Baker; Ian P. Crocker (Apoptosis, 2011)